Association of VEGF haplotypes with breast cancer risk in North-West Indians - Vasudha Sambyal; Kamlesh Guleria; Ruhi Kapahi; Mridu Manjari; Meena Sudan; Manjit Singh Uppal; Neeti Rajan Singh (BMC, 2021)
Abstract Background Angiogenesis is a complex and coordinated process regulated by different growth factors and is one of the hallmark features of cancer. VEGF is one of the most important endothelial cell mitogen and has a critical role in normal physiological and tumor angiogenesis. The objective of this study was to investigate the potential association of haplotypes of six VEGF polymorphisms with breast cancer risk in North-West Indians. Methods Samples of 250 breast cancer patients and 250 age and sex matched controls were genotyped for VEGF −2578C/A, −2549I/D, −460T/C, +405C/G, −7C/T and +936C/T polymorphisms. Haplotypes were generated to determine the better contribution of VEGF polymorphisms to breast cancer risk. Results Haplotypes CDTCCC (OR = 0.56, 95%CI, 0.38-0.81; p = 0.003) and CDTGCC (OR = 0.63, 95%CI, 0.44-0.92; p = 0.018) of VEGF −2578C/A, −2549I/D, −460T/C, +405C/G, −7C/T and +936C/T polymorphisms were significantly associated with decreased risk of breast cancer. CDTCCC haplotype was also significantly associated with reduced risk of breast cancer in pre and post menopausal as well as both obese and non obese patients. Haplotype CDTGCC was marginally associated (p = 0.07) with reduced risk of breast cancer in non-obese patients as compared with non-obese controls where as haplotype AICGTC was marginally associated (p = 0.09) with reduced risk of breast cancer in obese patients when compared with non-obese patients. The CDTGCC haplotype was significantly associated with increased risk of breast cancer in premenopausal obese patients (OR = 1.98, 95%CI, 1.10-3.56; p = 0.02). Conclusions Our data indicated that CDTCCC and CDTGCC haplotypes of VEGF −2578C/A, −2549I/D, −460T/C, +405C/G, −7C/T and +936C/T polymorphisms were significantly associated with breast cancer risk in North-West Indians. Further studies on multiethnic groups with larger sample size are required to confirm our results.